1990
DOI: 10.1128/jcm.28.11.2389-2393.1990
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation-aspiration for culturing draining decubitus ulcers: correlation of bacteriological findings with a clinical inflammatory scoring index

Abstract: Biopsy of infected decubitus ulcers for culture disrupts tissues and may disseminate infection. Antimicrobial prophylaxis to prevent dissemination of infection may adversely affect biopsy culture results. Irrigationaspiration to obtain submarginal specimens from draining decubitus ulcers was studied as an atraumatic, noninvasive culturing technique to serve as an alternative to biopsy in research activities. Two aspirates were obtained serially from 32 subjects; in 12 subjects, biopsies were also performed imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 18 publications
(27 reference statements)
1
6
0
Order By: Relevance
“…in two samples. These data are in good accordance with previous studies by Ehrenkranz et al . and Murray .…”
Section: Resultssupporting
confidence: 94%
“…in two samples. These data are in good accordance with previous studies by Ehrenkranz et al . and Murray .…”
Section: Resultssupporting
confidence: 94%
“…Besides, it is reasonable to expect that reliable, microbiological characterisation of infection as part of the management strategy will almost certainly increase the effectiveness of antimicrobial therapy beyond mere empiricism, resulting in reductions in antimicrobial waste and unnecessary antimicrobial prescribing, especially in countries with limited resources or with increasing occurrence of infections caused by antimicrobial‐resistant pathogens. Although none of the patients in our study had prior antimicrobial therapy before presenting to MNH with limb infections, published data suggest that recent antimicrobial treatment generally has no effect on the recovery of bacterial species in general (5).…”
Section: Discussionmentioning
confidence: 69%
“…A meta-analysis of 15 clinical studies 9,15,18,[21][22][23][24][25] evaluating the effectiveness of various CSS in 1056 chronic wounds found that pain was the only useful sign or symptom in diagnosing infection. 17 Other 'classic signs' of infection such as purulent exudate, erythema, heat and oedema had no predictive value in diagnosing infection, 17 which most studies classified as a bacterial load of 10 5 colony forming units/gram (CFU/g) or higher.…”
mentioning
confidence: 99%